2007
DOI: 10.1007/s00280-007-0642-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pure curcumin, demethoxycurcumin, and bisdemethoxycurcumin on WT1 gene expression in leukemic cell lines

Abstract: Pure curcumin, an excellent curcuminoid derivative, decreased WT1 gene expression in both transcriptional and translational levels. Thus, pure curcumin is one of a potential chemotherapeutic agent used for treatment of human leukemia. However, its chemotherapeutic property will need to be studied more in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Hydrogenated l-α-phosphatidylcholine from egg yolk (HEPC), soybean oil, polysorbate 80 (polyoxyethylene (20) sorbitanmonooleate, Tween 80), and chloroform were purchased from NacalaiTesque Inc., Kyoto, Japan. In HEPC, the phospholipid content was more than 99% and the phosphatidylcholine content was approximately 70%.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogenated l-α-phosphatidylcholine from egg yolk (HEPC), soybean oil, polysorbate 80 (polyoxyethylene (20) sorbitanmonooleate, Tween 80), and chloroform were purchased from NacalaiTesque Inc., Kyoto, Japan. In HEPC, the phospholipid content was more than 99% and the phosphatidylcholine content was approximately 70%.…”
Section: Chemicalsmentioning
confidence: 99%
“…Curcumin is effective for preventing and ameliorating gastric lesions. It also possesses anti-inflammatory [4], antibacterial [5,6], antifungal and antiyeast [7], antihypocholesterolemic [8], anticancer [9][10][11][12], antimutagen [13], antiparasitic [14], antitumorpromoting [15], antiproliferative [16], MDR modulator effects [17], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more and more studies have demonstrated the stronger activity of DMC when compared with curcumin in many aspects (8)(9)(10). Numerous studies have shown that DMC induces cytotoxic effects in many cancer cell lines such as colon (11) and renal cell cancer (12), glioma (9) and leukemic cell lines (13). However, no study exists which shows the effects of DMC on human lung cancer cells, and the role of DMC in inducing cell cycle arrest and apoptosis has never been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism may be that curcumin could suppress the activation of transcription factor NF-B [6][7][8] and signaling molecules related to carcinogenesis [9,10]. In vivo studies on rodent models further confirmed its anti-diabetes [11,12], antiAlzheimer's disease [13][14][15][16][17], and anti-tumorigenesis activities [18][19][20][21][22][23]. In addition, several clinical studies have revealed that curcumin is safe for human even at an oral dosage of 12 g per day [24,25].…”
Section: Introductionmentioning
confidence: 99%